Linear and Threshold Effect of CO2 Emissions, Economic Development, Clean Fuel and Technology on Health Expenditure in Central Asia - Inglesi-Lotz, Roula; Kuziboev, Bekhzod; Ibragimov, Jakhongir; Rajabov, Alibek; Liu, Jie; Abdullaev, Farkhod (International Journal of Energy Economics and Policy, 2024)
The investigation is a pioneer in examining the joint impact of CO2 emissions, economic development, access to clean fuel and technology, and threshold effect on health expenditure in Central Asia. For this purpose, the balanced panel dataset is built for 5 Central Asian countries, namely Uzbekistan, Kazakhstan, Kyrgyzstan, Tajikistan, and Turkmenistan, spanning 2000-2020 with annual data. The results of the Johansen cointegration test and error correction coefficients of VECM and ARDL show a long-run association among the studied variables. Granger causality test shows the causal effect from independent variables to dependent variables, further validating model construction’s relevance. According to the ARDL model findings, CO2 emissions, economic development, access to clean fuel, and technology positively impact health expenditure. Threshold regression results reveal that the economic development stage ( ) should be between 2326.36 and 2345.87 USD to increase health expenditure that can rationally respond to environmental degradation. Policy actions like renewable energy transition and enhancing economic development levels are proposed.